Prosedur Penerapan Dokumen Bill Of Lading Dalam Aktivitas Ekspor-Impor - FeviLia Dea Ayu; Ida Ayu Putu Widiati; I Wayan Arthanaya (Jurnal Analogi Hukum, 2020)
Abstract-The development and advancement of an industry in trade which is increasingly rapidly influencing the world economy, especially in international trade through exports and imports. The Bill of Lading in Indonesian is known as the "agreement" which is the most important shipping document in the process of shipping goods by sea transportation to reduce responsibility for the risks that will arise in international trade. Bill of Lading (B / L) is one of the important documents of the Letter of Credit (L / C) as a means of payment transactions for exporters and importers. So that the formulation of the problem used: 1) What is the role of the Bill of Lading documents in export-import activities? 2) What is the procedure for applying the Bill of Lading documents in export-import activities? The research method used is the normative legal research method so that the problem approach used is the legislation approach, and conceptual approach, and uses primary, secondary, and tertiary legal materials. So that the legal material collection technique used is the documentation technique by processing and analyzing legal materials that have been collected using legal arguments. The results of this study can be concluded that the regulation of the Bill of Lading (B / L) can be seen through the provisions of Article 506, the Commercial Law (KUHD); Article 25 paragraph (1) of Law No. 39 of 2007 concerning Excise. Keywords: Bill of Lading, International Trade, and Letter of Credit. Abstract-The development and advancement of an industry in trade which is increasingly rapidly influencing the world economy, especially in international trade through exports and imports. The Bill of Lading in Indonesian is known as the "agreement" which is the most important shipping document in the process of shipping goods by sea transportation to reduce responsibility for the risks that will arise in international trade. Bill of Lading (B / L) is one of the important documents of the Letter of Credit (L / C) as a means of payment transactions for exporters and importers. So that the formulation of the problem used: 1) What is the role of the Bill of Lading documents in export-import activities? 2) What is the procedure for applying the Bill of Lading documents in export-import activities? The research method used is the normative legal research method so that the problem approach used is the legislation approach, and conceptual approach, and uses primary, secondary, and tertiary legal materials. So that the legal material collection technique used is the documentation technique by processing and analyzing legal materials that have been collected using legal arguments. The results of this study can be concluded that the regulation of the Bill of Lading (B / L) can be seen through the provisions of Article 506, the Commercial Law (KUHD); Article 25 paragraph (1) of Law No. 39 of 2007 concerning Excise. Kata Kunci: Bill of Lading, transaksi international, surat kredit